HUBUNGAN INTERNAL LOCUS OF CONTROL DENGAN STRES AKADEMIK SISWA SMAN 2 CIMAHI - Siti Fatimah; Maya Masyita Suherman; Euis Eti Rohaeti; Ragil Amida Army Duntari; Riska Hidayat (Psikodidaktika, 2019)
Academic stress in students will arise when there is pressure for achievement both in the learning process and the interaction process in school. Academic stress is caused by the inability of students to process perceptions so that the achievement of the learning process is considered as academic demands that exceed the limits of their abilities and also the students' uncertainty about events in their lives can be controlled by themselves. This study aims to determine the relationship of internal locus of control and academic stress of students of SMAN 2 Cimahi. The subject of this research is the students of SMAN 2 Cimahi in the academic year 2018/2019. Measuring instruments in this study were academic stress scale (49 items; Î± = 0.875) and internal locus of control scale (30 items; Î± = 0.618). The method of data analysis in this study is Pearson correlation analysis. The results of Pearson correlation analysis based on the significance value p = 0.00 <0.05, which means that there is a relationship between internal locus of control and academic stress. The results of a simple correlation analysis (r) obtained a correlation between internal locus of control and academic stress of 0.610. This means that there is a strong relationship between internal locus of control and academic stress, while the direction of the relationship is positively significant, which means that the higher the internal locus of control, the academic stress will be lower. Internal locus of control effectively contributed 37.2% to academic stress, while 62.8% was determined by other variables not examined in this study.